Realtime Broiler Chicken Cage Control and Monitoring System - Iriani, Juli; Sitorus, Nobert; Gunoro; Abdullah; Cholish; Wahyudi; Meliala, Michael Doanta; Hasibuan, Rani Dame (MultiTech Publisher, 2024)
Control and monitoring systems in poultry farm cages are very necessary, especially for broiler farmers because the harvest process from growth to ready to harvest takes 30 to 35 days with a weight per tail between 1.5-2.0 kg. Important variables that are prioritized in broiler cages, namely temperature, humidity and lighting as well as the availability of feed and drinks on time, determine the quality and quantity of the broiler harvest. The solution to these problems requires a system that can work automatically with real-time monitoring features so that important variables in the chicken coop can be really well maintained. This research uses a combination of DHT11 temperature and humidity sensors, proximity sensors as sensors to check the availability of water and feed in containers, LDR light sensors and GY-302 Lux sensors, Real Time Clock timer modules to organize scheduling the availability of drinking water and chicken feed. These sensors will provide data to the ESP32 controller to control outputs such as heating and cooling and valves for opening and closing the stock of drinking water and feed. This system has also been integrated with the Internet of Things so that the condition of the chicken coop can be flexibly monitored remotely using a Smartphone or laptop utilizing the internet network. Based on the tests that have been carried out, it proves that the system has worked well in maintaining important variables in the chicken coop and has been well integrated based on the Internet of Things.